Epstein-Barr Virus-Positive T/NK-Cell Lymphoproliferative Diseases in Chinese Mainland - Ai, Junhong; Xie, Zhengde (Frontiers in Pediatrics, 2018)
Epstein-Barr virus-positive T/NK-cell lymphoproliferative disorders (EBV+ T/NK LPD) encompass a heterogeneous group of disorders, including chronic active Epstein–Barr virus infection (CAEBV), Epstein-Barr virus-associated hemophagocytic lymphohistiocytosis (EBV-HLH), systemic EBV+ T-cell lymphoma of childhood and hydroa vacciniforme-like lymphoproliferative disorder (HVLPD) and so on, predominantly affecting children and young adults with high mortality. Patients with EBV+ T/NK LPD have overlapping clinical symptoms as well as histologic and immunophenotypic features. In this review, we summarized the clinical features of EBV+ T/NK LPD in Chinese patients from the published articles.